An energetic derivative of 2, 2′, 4, 4′, 6, 6′-hexanitrostilbene (HNS) and its DMF solvate crystallized from HNS solution with tertiary amine additives. Issue 1 (2nd January 2019) - Cao, Xiong; Guan, Yuxiang; Yang, Liyuan; Yan, Mi; Ma, Qin; Fan, Guijuan; Liu, Yu; Huang, Shiliang
ABSTRACT: An energetic derivative of 2, 2′, 4, 4′, 6, 6′-hexanitrostilbene (HNS) and 2, 4, 7, 9-tetranitro-10 H -benzofuro[3, 2- b ]indole (TNBFI) has been synthesized from the N, N -dimethylformamide (DMF) solution of HNS with different tertiary amine additives, 4-(4-pyridyl)morpholine and 1, 1-bis(morpholino) ethylene. TNBFI crystallized with DMF in a solvate, TNBFI·2DMF, was identified by negative ESI mass spectrum and single-crystal X-ray diffractions. The 3D-supermolecular structure of TNBFI·2DMF was built from the alternate stacking of TNBFI and DMF layers with π-stacking interactions between TNBFI molecules and H-bonding interactions between TNBFI and DMF molecules. The energetic properties of TNBFI molecule as well as the thermal stability of its DMF solvate have been investigated.